Maximizing soybean yield by understanding planting date, maturity group, and seeding rate interactions in North Carolina. Issue 6 (19th September 2021) - Morris, Tristan C.; Vann, Rachel A.; Heitman, Josh; Collins, Guy D.; Heiniger, Ryan W.
Abstract: Growers across theU.S. Southeast use a diversity of soybean [ Glycine max  (L.) Merr.] planting dates, maturity groups, and seeding rates for soybean production depending on their rotational complexity. Studies were conducted across seven North Carolina environments in 2019 and 2020 to determine the effect of planting date (mid‐March through mid‐July), maturity group (MG 2–8), and seeding rate (185, 329–432, 434 seeds ha –1 ) on soybean emergence, stand, and yield. Across environments, soybean typically emerged more quickly with later planting dates; however, there were location‐specific variations in soybean emergence due to weather conditions around the time of planting. The longest and shortest emergence periods were 26 d for soybean planted in mid‐March and 4 d for soybean planted in June and July, respectively. In the higher yielding environments, yield was maximized with MG 3–4 cultivars planted at early April planting dates and yield declined as planting was delayed. In the low yield environments, yield was maximized with late April to mid‐May planting dates, typically with MG 5–7 cultivars. There was a penalty in both yield environments to planting past mid‐May and in the low yield environments for planting before mid‐April. Across environments, yields tended to be more similar among cultivars higher than MG 3 at planting dates in June and July. The effect of seeding rate on soybean yield was variable across planting dates, maturity groups, and yield environments. Future research is needed in North Carolina to validate the planting date and maturity group interactions on yield observed in this experiment to capture more variation in weather conditions. Core Ideas: Soybean emerged 4–26 d after planting depending on planting date and environment. In the high yield environments, highest soybean yields were achieved with early April planting. In lower yield environments, there was a yield penalty to planting before mid‐April. In all yield environments, delaying planting beyond late May resulted in yield declines. Yield was similar in late planting situations for MG 4—8.